2003
DOI: 10.1007/s10311-003-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Phototransformation and ecotoxicity of the drug Naproxen-Na

Abstract: The phototransformation of naproxen Na in aqueous medium has been investigated. Irradiation of the drug in drinking water affords seven photoproducts. Three of them are dimeric photoproducts isolated for the first time. The compounds, isolated by chromatographic processes, have been identified by spectroscopic means. The toxicity of the photoproducts and the parent drug has been assayed on Daphnia magna and Vibrio fischeri. The results indicate that some photoproducts are more toxic than naproxen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 9 publications
1
44
0
2
Order By: Relevance
“…We found that UV-A pre-irradiated samples caused deformations of the protozoan S. ambiguum, while they were not toxic to the crustacean T. platyurus. DellaGreca et al (2004b), studying the phototransformation of naproxen in aquatic medium, isolated a dimeric photoproduct that was 10 times more toxic to the crustacean Daphnia magna than the parent compound. The authors also identified very toxic photoproducts of prednisolone and dexamethazone (DellaGreca 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…We found that UV-A pre-irradiated samples caused deformations of the protozoan S. ambiguum, while they were not toxic to the crustacean T. platyurus. DellaGreca et al (2004b), studying the phototransformation of naproxen in aquatic medium, isolated a dimeric photoproduct that was 10 times more toxic to the crustacean Daphnia magna than the parent compound. The authors also identified very toxic photoproducts of prednisolone and dexamethazone (DellaGreca 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…Xenobiotics can undergo a variety of abiotic and biological processes in surface waters, including most notably the photochemical reactions. An important issue is that environmental transformation yields intermediates that are sometimes more stable and toxic than the parent compounds (DellaGreca et al, 2003). In addition to direct photolysis, indirect photochemistry can be important and it does not require the relevant pollutants to absorb sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is even more significant, because direct photolysis is the main sink of triclosan in surface waters [26]. Indeed, the photodegradation of a pollutant is not always beneficial to the environment, and the environmental and health impact of transformation products (TPs) is to be considered as well [28,29]. Another interesting example is the direct photolysis of the anti-epileptic drug carbamazepine that yields, amongst other TPs, mutagenic acridine ( Figure 3.12) [5,30,31].…”
Section: Direct Photolysismentioning
confidence: 99%